The Effect of Income Level, Financial Literacy, and Lifestyle on Employee Spending Levels at PT. Hi-Lex Cirebon - Mia Auliah; Abdul Nasir; Syaeful Bakhri (Citakonsultindo, 2026)
This study aims to analyze the influence of income level, financial literacy, and lifestyle on the level of expenditure of employees of PT. Hi-Lex Cirebon. This research is motivated by the increasing needs of employees' lives which are not always balanced with the ability to manage expenses. The research method uses a quantitative approach with a causal associative type. Data was obtained through questionnaires to 86 respondents who were selected using probability sampling using the random sampling method. Data analysis used multiple linear regression through t-test, F test, and determination coefficient. The results showed that the income level did not have a significant effect on the level of expenditure with a calculated t-value of 0.074 < 1.989 and a significance of 0.941 > 0.05. Financial literacy had a significant effect with a t-value of 2.127 > 1.989 and a significance of 0.036 < 0.05, while lifestyle had a significant effect with a t-value of 4.654 > 1.989 and a significance of 0.000 < 0.05. Simultaneously, the three variables had a significant effect on the level of expenditure with an F value of 21.285 > 2.70 and a significance of 0.000 < 0.05. An Adjusted R² value of 0.417 indicates that 41.7% of the variation in the level of expenditure can be explained by these three variables.